Efefct of Diaspididae (Hemiptera) pest on chlorophyll content and plant health in vanilla - Nur Hanani Zolkifli,; Suhaila Ab Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Vanilla plants are one of the crops that produce expensive spice and vanilla extract, or vanillin. A study of insect populations on vanilla plants was carried out at Kairos Plantation, Penang, Malaysia to determine the influence of the insect scale of the family Diaspididae on the photosynthetic pigment such as chlorophyll content in the vanilla leaves. A systematic collection of vanilla leaves to ensure that each leaf measured between 19 and 21 cm in length across two different vanilla species, (Vanilla tahitensis and V. planifolia). The leaves were meticulously gathered from the lower, middle, and top parts of the plant, followed by a detailed recording of the insects found on each leaf. The family Diaspididae also known as scale insects was identified as the primary herbivorous pest damaging the vanilla leaves. The lower part of V. tahitensis and V. planifolia leaves had more than 100 individuals of diaspidid and infestation on all studied leaves (level 5) and the severity was the greatest. There was a significant negative correlation between the height of vanilla plants and with infestation intensity of scale insects, r=-0.776, P=0.00. Vanilla plants that have been infested with scale insects showed loss of chlorophyll and carotenoids at different parts of the plant's height. Chlorophyll a, b and total chlorophyll content at the lower part of the leaves recorded the lowest values compared to the upper part of both vanilla species with significant results of chlorophyll a (F=22.87, P=0.002) and total chlorophyll (F=14.32, P=0.000). The photosynthetic pigments content in vanilla plants, namely chlorophyll a, chlorophyll b, and total chlorophyll, was highly influenced by the level of infestation and plant height. This shows that scale insect infestation had given negative impact on chlorophyll loss of the vanilla leaves in response by the plants to survive.